Correlation of extent of ALK FISH positivity and crizotinib efficacy in three prospective studies of ALK-positive patients with non-small-cell lung cancer. (13th July 2018) - Soria, J -C; Ho, S N; Varella-Garcia, M; Iafrate, A J; Solomon, B J; Shaw, A T; Blackhall, F; Mok, T S; Wu, Y -L; Pestova, K; Wilner, K D; Polli, A; et al.
Abstract: Background: In clinical trials of patients with anaplastic lymphoma kinase (ALK)-positive non-small-cell lung cancer (NSCLC) treated with crizotinib, evaluation of the relationship between the percentage of ALK-positive cells by fluorescence in situ hybridization (FISH)—particularly near the cut-off defining positive status—and clinical outcomes have been limited by small sample sizes. Patients and methods: Data were pooled from three large prospective trials (one single-arm and two randomized versus chemotherapy) of crizotinib in patients with ALK-positive NSCLC determined by Vysis ALK Break Apart FISH using a cut-off of ≥15% ALK-positive cells. Logistic regression and proportional hazards regression analyses were used to explore the association of percent ALK-positive cells with objective response and progression-free survival (PFS), respectively. Results: Of 11 081 screened patients, 1958 (18%) were ALK positive, 7512 (68%) were ALK negative, and 1540 (14%) were uninformative. Median percentage of ALK-positive cells was 58% in ALK-positive patients and 2% in ALK-negative patients. Of ALK-positive patients, 5% had 15%–19% ALK-positive cells; of ALK-negative patients, 2% had 10%–14% ALK-positive cells. Objective response rate for ALK-positive, crizotinib-treated patients with ≥20% ALK-positive cells was 56% ( n  =   700/1246), 55% ( n  =   725/1312) for those with ≥15% ALK-positive cells, and 38% for those with 15%–19% ALK-positive cells ( n  =   25/66). As a continuous variable, higher percentages of ALK-positive cells were estimated to be associated with larger differences in objective response and PFS between crizotinib and chemotherapy; however, tests for interaction between treatment and percentage of ALK-positive cells were not significant (objective response, P  =   0.054; PFS, P  =   0.17). Conclusions: Patients with ALK-positive NSCLC benefit from treatment with crizotinib across the full range of percentage of ALK-positive cells, supporting the clinical utility of the 15% cut-off. The small number of patients with scores near the cut-off warrant additional study given the potential for misclassification of ALK status due to technical or biologic reasons.